Parental personality, mental health, and fear of happiness as predictors of perceived coparenting relationship quality among mothers and fathers of preschoolers - Cynthia A. Frosch; Marcus A. Fagan; Wendy Middlemiss; Joohee G. Kim; Sheila R. Sjolseth (Australian Journal of Psychology, 2023)
Objective Existing theoretical models and research findings highlight individual parent characteristics as contributors to coparenting relationship quality. Yet less is known about how indices of parental personality, beliefs, and mental health symptoms relate to coparenting perceptions among parents of preschoolers. This study examines direct and indirect paths connecting parents’ Big Five personality traits, fear of happiness, and depression and anxiety symptoms with perceived coparenting quality. Method Using an online survey design, 160 parents (81 mothers; 79 fathers) of preschoolers (age 2–5 years) completed the Ten-Item Inventory of Personality, Fear of Happiness Scale, Patient Health Questionnaire-4, and Coparenting Relationship Scale – Brief Form. Results Parental Emotional Stability negatively related to anxiety and depressive symptoms and to fear of happiness. Anxiety symptoms and fear of happiness directly, and negatively, related to coparenting quality. Emotional stability was indirectly, positively related to coparenting quality via lower levels of parental anxiety and fear of happiness. Although parental depressive symptoms were unrelated to coparenting quality, parents’ Openness to Experience and fear of happiness positively predicted depressive symptoms. Conclusion Findings suggest parents’ anxiety symptoms and fear of happiness may underlie the processes by which parental Emotional Stability relates to perceived coparenting quality among parents of preschoolers.